The phosphatidylinositol‐transfer protein Nir2 binds phosphatidic acid and positively regulates phosphoinositide signalling. (30th July 2013) - Kim, SoHui; Kedan, Amir; Marom, Merav; Gavert, Nancy; Keinan, Omer; Selitrennik, Michael; Laufman, Orly; Lev, Sima
Abstract : Phosphatidic acid (PA) and phosphoinositides are metabolically interconverted lipid second messengers that have central roles in many growth factor (GF)‐stimulated signalling pathways. Yet, little is known about the mechanisms that coordinate their production and downstream signalling. Here we show that the phosphatidylinositol (PI)‐transfer protein Nir2 translocates from the Golgi complex to the plasma membrane in response to GF stimulation. This translocation is triggered by PA formation and is mediated by its C‐terminal region that binds PA in vitro . We further show that depletion of Nir2 substantially reduces the PI(4, 5)P2 levels at the plasma membrane and concomitantly GF‐stimulated PI(3, 4, 5)P3 production. Finally, we show that Nir2 positively regulates the MAPK and PI3K/AKT pathways. We propose that Nir2 through its PA‐binding capability and PI‐transfer activity can couple PA to phosphoinositide signalling, and possibly coordinates their local lipid metabolism and downstream signalling. Abstract : This study shows that the PI‐transfer protein Nir2 also binds to phosphatidic acid and that it translocates from the Golgi complex to the plasma membrane in response to growth factor stimulation. At the membrane it positively regulates the production of PI(4, 5)P2 and PI(3, 4, 5)P3 and concomitantly the MAPK and PI3K/AKT signalling pathways.